Design and Development of a Web-Based School Information System - Lontaan, Rolly Junius; Sinadia, Alfrits Roul (Fakultas Ilmu Komputer, Universitas Klabat, 2024)
The rapid development of information technology has had a significant impact on various fields, including education. This study aims to design and develop a web-based school information system for SMK Negeri 1 Sorong to enhance efficiency in data management and the dissemination of academic and non-academic information. The methodology used follows the Waterfall system development model, which includes requirements analysis, system design, implementation, testing, and maintenance. The research results indicate that the system, developed using PHP as the programming language and MySQL as the database, operates stably and provides users with flexible access. This system facilitates the integration of student data, teacher data, class schedules, and other related information. Testing confirmed that all system functions operate according to the designed specifications. With the implementation of this system, SMK Negeri 1 Sorong can improve the quality of educational services, simplify information access, and support digital transformation in the education sector. Furthermore, the results of this study have the potential to be applied and adapted in other educational contexts, particularly in the development of web-based school information systems that can be customized according to the needs of other educational institutions.